INFORMATION MODELING OF THE CONTENT QUALITY ASSESSMENT PROCESS DURING EXPERTISE OF TYPICAL LEARNING PLANS AND TYPICAL LEARNING PROGRAMS (CURRICULA) - Nurbekova, Ж.К.; Kussainov, Г.М.; Mikhalev, Р.К.; Tanirbergenova, А.Ш. (Bulletin of Abai KazNPU. Series of Physical and Mathematical sciences, 2021)
This article discusses the information modeling process of the quality assessment of content in the expertise of typical learning plans and typical learning programs (typical curricula). The results of the study of linear-concentrically constructed traditional and updated standard curricula and logical and technological map of the process of expertise of typical learning plans and typical learning programs (typical curricula) are presented. The problems of implementation associated with the meta-subject orientation of typical curricula are shown. A new form has been proposed, which provides for planning for each individual subject. Among the main substantive differences of the updated standard curricula, the following are considered: the values ​​of secondary education, the construction of programs in accordance with the expected results, the spiral construction of subject curricula, the taxonomy of educational goals, functional literacy, the adequacy of the content of sections and topics of academic disciplines to modern trends and focus on development and the formation of socially significant competences, etc. The improvement of the technology with a new algorithm for evaluating typical learning plans and typical learning programs (typical curricula) and making expert decisions is proposed. This study was carried out within the framework of the scientific and technical program "Scientific bases of modernization of the education and science system" at the National Academy of Education named after Y.Altynsarin of the Ministry of Education and Science of the Republic of Kazakhstan.